Photoactivation of Curcumin Doped Poly-Lactic-Co-Glycolic Acid Nanoparticles in Rat Model with Fixed Orthodontic Appliances - Sara Ghorbanpour; Maryam Pourhajibagher; Mohammad Noroozian; Hassanali Ghaffari; Abbas Bahador (The Scientific World Journal)
This study aimed to evaluate the antimicrobial effect of curcumin doped poly-lactic-co-glycolic acid nanoparticles (Cur-PLGA-Nps)-mediated antimicrobial photodynamic therapy (aPDT), as well as the probiotics on S. mutans in rats with fixed orthodontic appliances. Orthodontic appliances were ligated to the right maxillary of the rats. After the oral colonization of S. mutans, the rats were then treated in four groups including Cur-PLGA-Nps, light-emitting diode, Cur-PLGA-Nps-mediated aPDT, and probiotic (Lactobacillus acidophilus). After that, the S. mutans counts and the gtfB gene expression of S. mutans were determined on days 4, 7, 15, and 30. Probiotic and Cur-PLGA-Nps-mediated aPDT groups significantly reduced the count of S. mutans in a time-dependent manner (P<0.05). So, probiotics and Cur-PLGA-Nps-mediated aPDT were able to reduce S. mutans more than other groups on the 30th day. Also, there was no considerable difference between Cur-PLGA-Nps-mediated aPDT and probiotic groups in bacterial growth inhibition. The expression level of gtfB gene was significantly downregulated at all-time intervals after exposure to Cur-PLGA-Nps-mediated aPDT compared with untreated bacteria (P<0.05). According to the results, simultaneous use of Cur-PLGA-Nps-mediated aPDT and probiotic therapeutic approaches can be suggested to increase effectiveness.